PENGARUH LITERASI KEUANGAN FINANCIAL TECHNOLOGY, DAN TINGKAT PENDAPATAN, TERHADAP INKLUSIF KEUANGAN PADA KARYAWAN INDOMARET CABANG KELURAHAN BANGKA JAKARTA SELATAN - Tego Sugianto; Yunita Kurnia Shanti (Journal of Research and Publication Innovation, 2025)
This research aims to determine the influence of Financial Literacy, Financial Technology and Income Level on Financial Inclusion. The methodology used is quantitative. Where the sampling technique used a purposive sample totaling 47 employees. Data analysis uses descriptive analysis, validity and reliability testing, classical assumption testing, and hypothesis testing. 42 sample data were obtained. The type of data in this research is primary data with quantitative research methods. The analysis technique used is panel data regression analysis with a significance level of 5%. This research was processed using IBM SPSS V.24.00 software and shows that (1) financial literacy has no significant effect on financial inclusion, which means the hypothesis is accepted, and (2) financial technology has a significant effect on financial inclusion, which means the hypothesis is accepted, and (3) the level of income has a significant effect on financial inclusion, which means the hypothesis is accepted.